Vitamin D supplementation causes a decrease in blood cholesterol in professional rowers - Jastrzebski, Z.; Kortas, J.; Kaczor, K.; Antosiewicz, J. (Journal of Nutritional Science and Vitaminology, 2016)
In the skin vitamin D3 is synthesized from cholesterol, which leaves the question whether a feedback mechanism controlling the level of blood cholesterol exists. Here we investigate the effects of vitamin D3 supplementation on serum lipids in professional rowers. The rowers were divided into two groups following the same training schedule for 4 wk: one received placebo (TP) while the second received 5,000 IU of vitamin D3 every day (TD3). Plasma total antioxidant status, total triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL)-cholesterol (HDL-C), low-density lipoprotein (LDL)-cholesterol (LDL-C) and 25-hydroxyvitamin D (25-OH-D3) were determined in pre- and post-intervention. The ratios of TC/HDL-C and LDL-C/HDL-C were also calculated. Furthermore, maximal oxygen uptake was also measured at baseline. There were significant decreases over time in the TD3 group in TC 186±18 vs 163±21 (p<0.05) and HDL-C; LDL-C also decreased, but the changes were not statistically significant. Moreover, the supplementation caused a significant rise in blood 25-OH-D3 (+98%). Neither training nor vitamin D3 supplementation had an effect on total antioxidant status. In conclusion, the alterations in the lipoprotein profile seen in this study would suggest that effects of regular exercise on lipoprotein profile may linked to vitamin D3 status.